Identification of natural compounds as potential inhibitors of Interleukin-23: virtual screening, ADMET, drug-likeness, and dynamic simulation - Gheidari, Davood; Mehrdad, Morteza; Etedali, Mahan (Frontiers in Drug Discovery, 2025)
Introduction Psoriasis is a chronic, immune-mediated condition that affects approximately 100 million individuals worldwide. Interleukin 23 (IL-23) serves as a crucial pro-inflammatory cytokine in the pathogenesis of chronic inflammatory diseases associated with psoriasis. Monoclonal antibody therapies targeting IL-23 inhibit the overactive cytokine signaling that contributes to chronic inflammation across various organ systems. Over the past decade, IL-23 inhibitors have gained significant prominence in the treatment of psoriasis. Natural products have emerged as potential modulators of IL-23 activity, particularly in the context of inflammatory diseases such as inflammatory bowel disease (IBD). Several well-characterized phytochemicals, including sulforaphane, resveratrol, and curcumin, have demonstrated efficacy in inhibiting the production and function of Th17 cells, which are regulated by IL-23. However, the exploration of natural products specifically related to psoriasis has been limited.MethodsThis study aimed to identify novel candidates derived from natural products for the treatment of psoriasis. To achieve this, 60,000 natural compounds were filtered according to the rule of five (Ro5) and obtained from the ZINC database. These ligands underwent high-throughput virtual screening (HTVS) in molecular docking studies against the IL-23 receptor. The top 50 ligands were subsequently re-evaluated using standard precision (SP), and for enhanced accuracy, the top 19 from the SP protocol were further screened using the extra precision (XP) protocol.Results and Discussion The computational screening revealed that the docking energy values for the nineteen ligands binding to the target enzyme ranged from -3.669 to -7.143 kcal/mol. Among these, ligand 1 (L1) exhibited the highest binding energy at -7.143 kcal/mol with IL-23. Molecular dynamics (MD) simulation further confirmed the stability of the IL-23-L1 complex, highlighting a robust interaction between L1 and the target enzyme, with Tyr100 being one of the amino acids showing the highest frequency of interaction throughout the simulation. Density functional theory (DFT) analysis using the Becke, three-parameter, Lee-Yang-Parr (B3LYP)/6-31++G(d,p) basis set indicated a promising reactivity profile for the ligands. The analysis of absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties suggested that all inhibitor ligands possess favorable pharmacological characteristics, including appropriate molecular weight, lipophilicity, hydrogen bond donors and acceptors, molecular refractivity, topological polar surface area (TPSA), and the number of rotatable bonds, all in accordance with Ro5. Additionally, the physicochemical properties indicate that most ligands are capable of human intestinal absorption (HIA) and possess a wide therapeutic index, suggesting a favorable safety profile.